Candida albicans Shaving to Profile Human Serum Proteins on Hyphal Surface - Marín, Elvira; Parra-Giraldo, Claudia M.; Hernández-Haro, Carolina; Hernáez, María L.; Nombela, César; Monteoliva, Lucía; Gil, Concha (Frontiers in Microbiology, 2015)
Candida albicans is a human opportunistic fungus and it is responsible for a wide variety of infections, either superficial or systemic. C. albicans is a polymorphic fungus and its ability to switch between yeast and hyphae is essential for its virulence. Once C. albicans obtains access to the human body, the host serum constitutes a complex environment of interaction with C. albicans cell surface in bloodstream. To draw a comprehensive picture of this relevant step in host-pathogen interaction during invasive candidiasis, we have optimized a gel-free shaving proteomic strategy to identify both, human serum proteins coating C. albicans cells and fungi surface proteins simultaneously. This approach was carried out with normal serum (NS) and heat inactivated serum (HIS). We identified 214 human and 372 C. albicans unique proteins. Proteins identified in C. albicans included 147 which were described as located at the cell surface and 52 that were described as immunogenic. Interestingly, among these C. albicans proteins, we identified 23 GPI-anchored proteins, Gpd2 and Pra1, which are involved in complement system evasion and 7 other proteins that are able to attach plasminogen to C. albicans surface (Adh1, Eno1, Fba1, Pgk1, Tdh3, Tef1 and Tsa1). Furthermore, 12 proteins identified at the C. albicans hyphae surface induced with 10% human serum were not detected in other hypha-induced conditions. The most abundant human proteins identified are involved in complement and coagulation pathways. Remarkably, with this strategy, all main proteins belonging to complement cascades were identified on the C. albicans surface. Moreover, we identified immunoglobulins, cytoskeletal proteins, metabolic proteins such as apolipoproteins and others. Additionally, we identified more inhibitors of complement and coagulation pathways, some of them serpin proteins (serine protease inhibitors), in HIS versus NS. On the other hand, we detected a higher amount of C3 at the C. albicans surface in NS than in HIS, as validated by immunofluorescence.